Republic of Armenia : Third Reviews Under the Extended Fund Facility and Extended Credit Facility, and Request for Modification of Performance Criteria: Staff Report; Staff Supplements; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Armenia. (IMF Staff Country Reports; Country Report ;, 2011)
Armenia's growth has picked up in 2011, led by manufacturing, mining, and services, while agriculture has rebounded from the collapse. Credit continues to grow rapidly, particularly in foreign currency and based on strong inflows to banks. Inflation has come down sharply, reflecting policy rate hikes, spending restraint, the agriculture recovery, and favorable global price developments. Challenges include safeguarding financial system stability, strengthening tax revenues to ensure sustainability and support pro-growth and pro-poor spending, improving the business environment to enhance growth and reduce poverty and unemployment, and reducing external imbalances.